2015
DOI: 10.1007/s10040-015-1314-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flow velocity and spatial heterogeneity on DNAPL migration in porous media: insights from laboratory experiments and numerical modelling

Abstract: Understanding the migration of dense non-aqueous phase liquids (DNAPLs) in complex subsurface systems is important for evaluating contamination source zones and designing remediation schemes after spill events. Six sandbox experiments were performed to explore the individual effect of flow velocity, and the combined effect of flow velocity and layered lenses on a DNAPL (PCE) migration in porous media. DNAPL saturation was measured using a light transmission system, and saturation distribution was quantified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…As expected the spill in the hydrophilic only material resulted in the DNAPL migrating downward with very little lateral spread until it came into contact with the fine grained material at the bottom of the box (Taylor et al 2001, Zheng et al 2015, Zheng et al 2016. As the DNAPL pooled at the bottom of the box it began to spread laterally across the bottom of the box.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As expected the spill in the hydrophilic only material resulted in the DNAPL migrating downward with very little lateral spread until it came into contact with the fine grained material at the bottom of the box (Taylor et al 2001, Zheng et al 2015, Zheng et al 2016. As the DNAPL pooled at the bottom of the box it began to spread laterally across the bottom of the box.…”
Section: Discussionsupporting
confidence: 56%
“…This meant that the majority of transducers never came into contact with the DNAPL and the transducers at the bottom of the box were placed too high to record any of the pooling that occurred as the DNAPL came into contact with the fine grained layer. Although the spills in this work were conducted under static conditions, work by Zheng et al (2015) found that in homogeneous media the lateral and vertical migration of a DNAPL spill was significantly altered by increasing flow velocity.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, Cnudde and Boone [20] proved that image analysis is a reliable technique for rock pore space direct imaging and direct investigation of liquid migration. Therefore, a number of researchers [7], [14]- [17], and [21]- [23] have carried out image analysis techniques for liquid migration experiment. As mentioned by Maas and Hampel [24], image analysis technique in civil engineering field was regularly used to study the object flow absorption and liquid migration of small properties specific to structure crack extension.…”
Section: Regional Conference In Civil Engineering (Rcce)mentioning
confidence: 99%
“…We speculate that the heterogeneity retarded the vertical infiltration of CB, leading to its extended lateral spread. Compared to the homogeneous porous media, the layered heterogeneous porous media combined with the Fe-Cu/biochar system increased the lateral spread of the CB distribution, thereby lowering the effluent CB concentration [39]. Figures 5 and 6 show the breakthrough curves of the tracer experiments, representing the ratio between the concentration of sodium chloride (NaCl) in the column outlet to its concentration in the column inlet, denoted by ratio between current and initial concentration (C/C 0 ).…”
Section: Released Iron Ion Concentration In Effluentsmentioning
confidence: 99%